Effect of company's age and audit firm size on voluntary corporate social disclosure among selected listed manufacturing companies in Nigeria - Segun Idowu Adeniyi (Trends Economics and Management, 2020)
Purpose of the article: In Nigeria, it is not compulsory for listed companies to report their corporate social responsibility in their financial report. However, some firms are reporting their social responsibility to their stakeholders, while some companies fail to do so. Some studies conducted on the influence of the company's age and audit firm size on voluntary corporate disclosure showed inconsistent results and methodology differences indicate a research gap which this study tends to examine. Methodology/methods: This study used ex-post facto design. Out of thirty seven (37) consumer and industrial goods manufacturing companies listed in Nigeria as of December, 2018, only thirty (30) firms have their financial statements for the period 2008 to 2018 available either on their website or in the office of the Nigerian Stock Exchange. We applied the linear regression analysis with the aid of the SPSS 20.0 software for the panel data analysis. Scientific aim: This study investigates the effect of the company's age and audit firm size on voluntary corporate social disclosure of the selected listed manufacturing firms in Nigeria. Findings: The company's age does not have positive significant effect on voluntary corporate social disclosure. Contributions: The study shows that some young firms and older firms engaged in voluntary corporate social reporting, therefore regulatory authorities should make it compulsory for all listed firms on the Nigerian Stock Exchange to disclose their corporate social responsibility.
Keywords: M15; M21; 650; company's age; audit firm size; manufacturing firms; stakeholders; voluntary corporate social disclosure